The evolution of the super-whale. Complexity and simplicity in environmental communication. (January 2019) - Singleton, Benedict E.
Abstract: This article discusses the tendency within environmental communication to homogenise diverse situations. Utilising the case of whale conservation it describes how actors on both sides of the whaling debate utilise the 'super-whale' – a homogenised discursive construct. The article argues that there are pragmatic advantages to such framing of environmental situations but also costs. In the case of whale conservation, the super-whale maintains focus on whaling rather than other, arguably more pressing, threats to whale species. More generally, utilising such framing tactics arguably prevent the voicing of new narratives about the global social order.